Identifikasi Pengetahuan dan Kompetensi Sains Siswa Berdasarkan Socio-Scientific Issues (SSI) pada Materi Sistem Koloid - Nurmilawati, Siti; Agung, Salamah; Murniati, Dewi (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This study aimed to determine student’s knowledge and science competence based on socio-scientific issues (SSI) of colloidal system material. A total of 313 class XII students in four schools representing South Tangerang City High School participated in this study. Sampling was done using cluster random sampling technique. The method used in this research is quantitative descriptive method with survey research. The instruments used were 22 essay questions. The obtained quantitative data were analyzed by scoring and converted into percentages. Based on the results of the study, it showed that the scientific literacy ability of students on aspects of science knowledge and competence is in quite good category with the percentage of achievement obtained respectively at 58.39% and 57.89%. Keywords: Science Literacy, Socio-Scientific Issues, Colloidal Systems